Blood–brain barrier permeability changes in dogs with suspected canine cognitive dysfunction using magnetic resonance imaging subtraction enhancement analysis - Merbl, Yael; Mondrus, Ella; Hanael, Erez; Shamir, Merav H. (Frontiers in Veterinary Science, 2025)
BackgroundBlood–Brain Barrier (BBB) breakdown/ dysfunction (BBBD) has been recognized as a contributing factor to cognitive decline in degenerative diseases and the normal aging process in the elderly. There is a need for antemortem evaluation tools to assess the permeability of the BBB in cases of canine cognitive dysfunction (CCD), allowing for better grading of the dysfunction and monitoring of its progression.Hypothesis/objectivesThis study aims to examine changes in the BBB permeability using magnetic resonance imaging (MRI) in dogs with CCD compared to a control group. We hypothesized that changes in BBB permeability would be detected and quantified using subtraction enhancement analysis (SEA).AnimalsMRI scans of dogs with signs of CCD were received from the Koret Veterinary Teaching Hospital (n = 10, 0.35 T MRI) and WSU (n = 3, 1.5 T MRI) and compared to non-CCD dogs (n = 9 from Koret, n = 6 from WSU).MethodsThis is a retrospective case–control study. MRI scans were analyzed using SEA to determine a threshold value of “positive-permeable” voxels, which was then used to highlight suspected areas and calculate a score for BBB dysfunction (BBBD).ResultsMean BBBD scores did not differ significantly between the study and control groups. BBBD was present in a few cases of CCD, but not in all.Conclusion and clinical importanceSEA was less effective in recognizing BBBD in dogs with CCD compared to those with other canine diseases such as neoplasia and seizures. It may be necessary to explore alternative methods to increase the sensitivity of BBBD detection for CCD, or it may that BBBD occurs only in a subpopulation of patients.